Media Baru: Tantangan dan Peluang Dakwah - Rubawati, Efa (Jurnal Studi Komunikasi, 2018)
This book describes Da'wah in the New Media Era. The presence of the Internet with the characteristics of interactivity and connectivity, making a new paradigm in preaching. Da'i is no longer the main factor of receiving the message of da'wah maximally by mad'u (object of da'wah) because in the networking society, mad'u not only receive passive message of da'wah, they are actively processing and interpreting the message -the message they receive and reshare it in their social media. This becomes a challenge as well as da'wah opportunities, the challenge lies in how the messages of dakwah are not predicted by the logic of the media as well as the understanding of the recitation of the message preachers. But the opportunity to get the messages of dakwah quickly and wisely makes the new media into an effective medium in the activities of propaganda today